An intersection-based coverage algorithm for PEGASIS architecture in Wireless sensor networks - Young-Long Chen; Yu-Cheng Lin; Neng-Chung Wang (2012 International Conference on Machine Learning and Cybernetics, 2012)
In Wireless sensor networks (WSNs), the energy of sensor node is finite, it's an important issue that how to reduce the energy consumption and extend the lifetime of entire network. In power-efficient gathering in sensor information systems (pEGASIS) topology architecture, the energy consumption of each sensor node is fewer and more average than low-energy adaptive clustering hierarchy (LEACH). Accordingly, we combine the PEGASIS topology architecture and intersection-based coverage algorithm (IBCA) to decrease the energy consumption. First of all, we find out the redundant sensor nodes to enter to the sleep mode by means of IBCA. Then, it builds the PEGASIS topology architecture by active sensor nodes which are not chosen to enter to sleep mode by IBCA. Through a series of simulations, the performances of our novel scheme outperform LEACH with PBCA in terms of energy consumption, number of alive nodes and sensing areas.